Effect of partial substitution of wheat flour with freeze-dried olive pomace on the technological, nutritional, and sensory properties of bread - Dahdah, Patricia; Cabizza, Roberto; Farbo, Maria Grazia; Fadda, Costantino; Del Caro, Alessandra; Montanari, Luigi; Hassoun, Georges; Piga, Antonio (Frontiers in Sustainable Food Systems, 2024)
In the last years, olive pomace, a by-product of olive oil extraction, has shown great interest. The work aims to valorize the olive pomace of two Sardinian olive cultivars, Bosana and Semidana, by incorporating them into the formulation of functional baked products to improve their nutritional value. The freeze-dried pomace of the two varieties has been used to substitute the type 00 flour in percentages of 1%, 2%, and 3% (w/w). The olive pomace was characterized by macro-composition analysis, while the bread samples were characterized for their proximate, physical, technological, sensory characteristics and shelf life. The specific volume of fortified samples decreased significantly compared to the control, while antioxidant activity, and nutritional parameters were significantly improved using olive pomace. Moreover, fortified samples showed a reduction of browning and whiteness indices with respect to control. Textural profile analysis showed a firmer product, compared to the control, with higher levels of olive pomace which also positively affected the cell size distribution in the crumb. Sensorially, consumers were mostly appealed by the 1% levels of substitution of olive pomace, in particular that of the Bosana. Hardness of all samples increased significantly along 7 days of storage thus resulting in a shelf life of less than 3 days. Therefore, it can be concluded that the incorporation of olive pomace, especially at low levels (1%), into white bread significantly improves the nutritional and sensorial quality of bread without significantly affecting its technological properties.